2012
DOI: 10.1039/c2cc34601j
|View full text |Cite
|
Sign up to set email alerts
|

Fast and reversibly switchable wettability induced by a photothermal effect

Abstract: We report a novel approach for the fabrication of a photo-responsive surface with fast and reversibly switchable wettability between hydrophobicity and hydrophilicity induced by a photothermal effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…The hydrophobicity of the nano­fibrous membranes is seen to increase with increase in the concentration of PNIPAM. This transition from hydrophilic to hydrophobic state is due to the intermolecular hydrogen bonding of the PNIPAM chains among themselves and also with CA (Figure S3, Supporting Information) . When the temperature is reduced to 23 °C (room temperature), the membranes attain superhydrophilic state due to the inherent hydrophilic nature of CA and PNIPAM and also due to the intermolecular hydrogen bonding between PNIPAM and CA chains with water molecules.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The hydrophobicity of the nano­fibrous membranes is seen to increase with increase in the concentration of PNIPAM. This transition from hydrophilic to hydrophobic state is due to the intermolecular hydrogen bonding of the PNIPAM chains among themselves and also with CA (Figure S3, Supporting Information) . When the temperature is reduced to 23 °C (room temperature), the membranes attain superhydrophilic state due to the inherent hydrophilic nature of CA and PNIPAM and also due to the intermolecular hydrogen bonding between PNIPAM and CA chains with water molecules.…”
Section: Resultsmentioning
confidence: 99%
“…This transition from hydrophilic to hydrophobic state is due to the intermolecular hydrogen bonding of the PNIPAM chains among themselves and also with CA ( Figure S3, Supporting Information). [ 33 ] When the temperature is reduced to 23 °C (room temperature), the membranes attain superhydrophilic state due to the inherent hydrophilic nature of CA and PNIPAM and also due to the intermolecular hydrogen bonding between PNIPAM and CA chains with water molecules. This results in high surface energy and very low water contact angle (Table 1 and Tables ST1-ST3, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…While both irreversible and reversible switching in surface wettability as a result of photochemical transformations have been demonstrated previously by many groups, the photothermal effect to control wettability of interfaces is rarely explored. In one very recent example known to us, the photothermal effect was used to control wettability of a surface, coated with a polyelectrolyte multilayer, which contained assembled AuNPs, modified by grafted PNIPAM homopolymer chains after film assembly . Here, we use premodified, polymer‐grafted AuNPs as units for surface immobilization, and, more importantly, explore modified by block copolymer rather than homopolymer brushes.…”
Section: Resultsmentioning
confidence: 99%
“…In one very recent example known to us, the photothermal effect was used to control wettability of a surface, coated with a polyelectrolyte multilayer, which contained assembled AuNPs, modifi ed by grafted PNIPAM homopolymer chains after fi lm assembly. [ 43 ] Here, we use premodifi ed, polymer-grafted AuNPs as units for surface immobilization, and, more importantly, explore modifi ed by block copolymer rather than homopolymer brushes. The use of dually responsive block copolymers to modify plasmonic nanostructures broadens the palette of stimuli, which can be applied to these nanostructures.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12] The controllable self-healing using light irradiation can be used to obtain gradients and patterns, which are of great signicance in microuidics, bioarrays, liquid self-transport and so on. In recent years, several scientists have found that molecules could be released from capsules or particles via irradiation of light with high spatial and temporal controllability.…”
Section: Introductionmentioning
confidence: 99%